2020
DOI: 10.2147/idr.s250158
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Existence of High Bacterial Resistance to Some Reserved Antibiotics in Tertiary Hospitals in Tanzania: A Call to Revisit Their Use</p>

Abstract: Background: Antibiotic resistance poses burden to the community and health-care services. Efforts are being made at local, national and global level to combat the rise of antibiotic resistance including antibiotic stewardship. Surveillance to antibiotic resistance is of importance to aid in planning and implementing infection prevention and control measures. The study was conducted to assess the resistance pattern to cefepime, clindamycin and meropenem, which are reserved antibiotics for use at tertiary hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 30 publications
6
18
0
Order By: Relevance
“…Of the isolates tested, (66.7%) were resistant to Cefoxitin and classified as MRSA infection. This observation corroborates with that recently reported at Muhimbili National Hospital and Bugando Medical Centre (61%), 18 and those from other sub-Saharan Africa countries; Kenya (53.5%), 31 Rwanda (82%) 32 ) and Eretria (72%). 32 S. aureus isolates also exhibited resistance to Erythromycin, Tetracycline, and Notes: Three P. aeruginosa isolates were tested for CAZ, 1 (33.3%) isolate was resistant (results not shown in this Table).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Of the isolates tested, (66.7%) were resistant to Cefoxitin and classified as MRSA infection. This observation corroborates with that recently reported at Muhimbili National Hospital and Bugando Medical Centre (61%), 18 and those from other sub-Saharan Africa countries; Kenya (53.5%), 31 Rwanda (82%) 32 ) and Eretria (72%). 32 S. aureus isolates also exhibited resistance to Erythromycin, Tetracycline, and Notes: Three P. aeruginosa isolates were tested for CAZ, 1 (33.3%) isolate was resistant (results not shown in this Table).…”
Section: Discussionsupporting
confidence: 92%
“…The majority of P. aeruginosa isolates were recovered from wound pus and ear pus and the pathogen was highly resistant to Ampicillin, Amoxicillin-Clavulanic Acid, Gentamicin, Ceftriaxone, Tetracycline, Nalidixic Acid, and Meropenem but more susceptibility to Ciprofloxacin. Resistance to Meropenem was 66.7%, relatively higher than the 55.2% reported by Mikomangwa et al (2020) 18 and 19% in a study conducted at Bugando Medical Centre using isolates collected between 2012 and 2017. 29 This suggests that P. aeruginosa is increasingly becoming resistant to antibiotics.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Similar results were revealed by Saderi and Owlia . [27]who reported that (55.7%) of P. aeruginosa isolates were susceptible to imipenem.…”
Section: Discussionmentioning
confidence: 99%